Nacionalinių žmogaus teisių apsaugos ataskaitų teikimo ir tolesnių veiksmų mechanizmų (NMRF) reikšmė: šių naujų pasaulinių vidaus procesų vertinimas pagal Gruzijos ir Portugalijos pavyzdžius - Sarkin, Jeremy (Teisė, 2019)
This article reviews domestic human rights institutions called Mechanisms for Reporting and Follow-Up (NMRFs). The article scrutinizes how important state reporting on human rights has become, and then evaluates what NMRFs are, and what the different models of NRMFs are. The article focuses on the nations of Georgia and Portugal.